استخدام المدخل ألابتکاری فی تحلیل وحل مشکلات أسلوب الإحالةفی مناقصات المشاریع الإنشائیة - nan, nan; nan, nan (Iraqi Journal of Civil Engineering, 2007)
The construction projects are designed and implemented according to the needs of the employer and according to reasonable program and cost, and if the employer is not the performer in this case he needs an experience constructor and adequate capacity to assume responsibilities for all phases of the project implementation .the challenges facing the construction industry in Iraq, especially in the current circumstances necessitate the workers serious thought in order to advance progress in construction area for the better. The research idea has crystallized on the subject (choosing the most appropriate tender) with a study of application case for construction projects in Iraq due to the emergence of tenders referral to bids least price or referral to certain companies without competition and consequently the emergence of serious problems including humanitarian problems and economic and otherwise. Since corruption in the contracts implementation and conclusion is a major disaster on the industrialized and developing countries a like , especially when bribe money is large and when man prefers money to values, the result will be poor construction quality, weak management and this what can be seen in construction sector in Iraq, the time being.